Influence of characteristics of marine macroalgae on feeding preferences of the milkfish (Chanos chanos) in Peninsular Malaysia / Lim Wai Yin - Lim, Wai Yin (2020)
Herbivores can alter several ecological mechanisms including interactions between native and non-native autotrophs that may determine invasion success of the non-native autotrophs. This study looked into the autotroph-herbivore interactions in coastal marine ecosystems of Peninsular Malaysia, mainly to determine if autotroph nutritional components and geographical differences significantly influence herbivore feeding behaviours. The relative consumption rate (RCR) of milkfish (Chanos chanos Forsskål), a generalist herbivore obtained from the Straits of Malacca was documented through feeding trials using 12 macroalgal species collected from different coastal areas of the Straits of Malacca, the Straits of Johor, and the South China Sea. The herbivore was observed to feed selectively (P<0.05) on the tested macroalgal species, with Valoniopsis pachynema (G.Martens) Børgesen and Cladophora prolifera (Roth) Kützing from the coastal areas of the South China Sea has the highest RCR (94.04 mg g-1 day-1 and 78.20 mg g-1 day-1, respectively). Contrarily, Padina gymnosphora (Kützing) Sonder collected from the Straits of Johor was the least preferred species with the lowest RCR (1.74 mg g-1 day-1). Based on the nutritional analysis, the most consumed species V. pachynema and the least consumed species P. gymnosphora had the lowest and highest total nitrogen content, respectively. A significant inverse correlation was found between the RCR and total nitrogen content of macroalgae, implying the possibility of nutrient-specific compensatory feeding by the herbivore. Besides total nitrogen content, the RCR was also negatively correlated with total phenolic content, where the least consumed species P. gymnosphora recorded the highest total phenolic content. This study also found that the morpho-functional groups of macroalgae may exert influence over herbivore feeding preferences, whereby two tested filamentous macroalgae were consumed in greater amounts than species from other functional groups such as corticated foliose macroalgae. The overall findings demonstrate that the feeding behaviours of a generalist herbivore may depend directly or indirectly on multifaceted factors, including the nutritional quality, novelty, and morphology of the autotrophs.